Trends in Offensive Team Activity in Basketball - Boris Bazanov; Priit Võhandu; Rein Haljand (Lithuanian Sports University, 2018)
The purpose of this paper is to analyze the structure of the models of offense and to determine their efﬁ ciency. We were able to determine the teamwork structure by using a system of analysis of the offensive process. The analysis of the team activity as an integrated whole becomes very important. For this research we observed the Tallinn University basketball team, which plays in Division One of the Estonian league. The data was gathered from 600 ball possessions in 8 recorded games of the regular season. The data we collected was analyzed by the means of data mining. This research has helped to work out the basics of the analytical system of the teamwork aspect. The analyzing system of the competitive activity of the game, enables us to ﬁ nd out interesting offensive models from the data. The results show that the team scoring (points/possession) as the main indicator of analyzed offenses was equal to 1.13 on average with a frequency of 48%. The 1-2 s duration period of ball possession in offensive zone proves to be most effective (scoring 68%). The most effective transition period is under 1.82 s (62%). The scoring of set offense is 44% in the mean. On the basis of this information, the coach can ﬁ nd more convenient time lapses in the game's performance. The analyzing system worked out through that, helps coaches to develop performance and promote learning. Keywords: performance analysis, data mining, efficiency.